The "appropriate adult": What they do and what they should do in police interviews with mentally disordered suspects. (7th April 2019) - Farrugia, Laura; Gabbert, Fiona
Abstract: Background: In almost all countries worldwide, the first point of contact with the criminal justice system is with the police. A large proportion of these individuals may have vulnerabilities, such as mental health difficulties. Given the complexities associated with vulnerable suspects, such interviews may be compromised, which could lead to a miscarriage of justice. In England and Wales, the Police and Criminal Evidence Act (PACE) 1984 and its accompanying Codes of Practice lay down requirements for interviewing vulnerable suspects and provide for attendance of "appropriate adults" to support communication between police and the vulnerable suspect. To date, however, their role has been underresearched. Aims/Hypotheses: To explore the role of appropriate adults in police interviews and test the hypotheses, first, that appropriate adults more commonly remain passive during interview than expected from guidance and, second, that any interventions are more likely than not to follow examples in current guidance. Methods: Transcripts of police interviews conducted with suspects with possible mental disorder and an appropriate adult present ( N = 27) were analysed using a specially developed coding framework. Results: Appropriate adults were significantly more likely to remain passive than to intervene, even when current guidance would suggest intervention. When they did intervene, however, such interventions were significantly more likely than not to follow from guidance than the vulnerable suspect's needs. Police and Criminal Evidence Act (PACE) 1984. Conclusions/implications for practice: In our sample, appropriate adults were not fulfilling their role as outlined in the Police and Criminal Evidence Act (PACE) 1984 and accompanying Codes of Practice; specifically, they appeared to know what to do but not when to do it. There is a heightened risk of a miscarriage of justice in such circumstances without improvements.